Potencial de desarrollo y gestión de la política regional. El caso de Chihuahua - Luis Enrique Gutiérrez Casas (Frontera Norte, 2007)
This essay describes the regional development potential model and proposes a reviewed version of Biehl approach. Based on this model it is introduced a classification system capable of characterizing different regional contexts and anticipate public policies for specific territorial problems. The case of study is the mexican northern state of Chihuahua. The findings of this study validates the model as an analytical toolnon-substitute but complementary to the set of models and instruments used by regional economics, and gives practical information in order to planning development policies for the municipalities of Chihuahua.